DANUBE AND DANUBE REGION – IMPLICATION ON RURAL DEVELOPMENT IN SERBIA - Gajić, Milivoj; Koviljko, Lovre; Zekić, Stanislav; Kresoja, Marinko (Economics of Agriculture, 2011)
The history of the Danube countries was marked by conflict in pursuit of achieving a wide range of individual interest, defning the long-term relationships between them. However, over the last half a century, these countries have been searching for the common interests, in order to use the natural resources of the Danube basin more effectively. Danube waterway is immensely important for all Danube countries due to the Rhine-Main-Danube canal which links North with Black Sea. At the same time, the frequency of this form of transport requires the adoption of numerous regulations aimed at ensuring free navigation on the Danube. Of course, this has to be done in a subtle way, aligning individual interests in order not to violate the sovereignty of the Danube countries. Danube waterway through Serbia greatly facilitates communication with neighboring countries, and further the European Union. This has opened the possibility for improvement of economic conditions through diversifcation of economic activities, promotion of rural tourism development and hence the development of rural regions in the Danube basin.